Descriptions Of Self-Criticism and Self-Forgiveness as a Result of Parental Verbal Violence on Early Adulthood - Adilah Ihsany; Yossy Dwi Erliana (Indonesian Journal of Behavioral Studies, 2022)
This study aims to determine the descriptions of self-criticism and its protective characteristics, namely self-forgiveness in early adulthood individuals who had experienced verbal abuse from their parents. This research uses qualitative research with descriptive design. The result of this study shows that the two subjects experienced both forms of self-criticism, namely inadequate self and hated self as a result of verbal abuse by parents. Both subjects also experienced the stages of avoidance motivation, revenge motivation and benevolence motivation to achieve self-forgiveness.